Leucocyte adhesion deficiency presenting as a chronic ileocolitis. Issue 4 (October 1996) - D'Agata, I D; Paradis, K; Chad, Z; Bonny, Y; Seidman, E
Abstract : CD11/CD18 leucocyte glycoprotein deficiency is a rare, congenital adhesion molecule disorder which, in its severe form, is usually fatal. Leucocytes in affected subjects have abnormal migration and adherence, rendering patients susceptible to life threatening infections. The CD11/CD18 integrins, and other adhesion molecules, are considered essential to the normal inflammatory response. It has been postulated that adhesion molecules may be responsible for mediating in part, the inflammatory changes observed in inflammatory bowel diseases and related disorders. This report describes the first case of CD11/CD18 deficiency characterised by a chronic ileocolitis. Bone marrow transplantation completely resolved the gastrointestinal symptoms, supporting a role for neutrophil dysfunction in the pathogenesis of the gut lesions. This case suggests that specific blockade of CD11/CD18 integrins alone may not halt the chronic inflammatory response observed in immune mediated bowel disorders, and that abnormalities of leucocyte function must be included in the differential diagnosis of paediatric Crohn's disease.